2015
DOI: 10.1186/s12889-015-1969-x
|View full text |Cite
|
Sign up to set email alerts
|

The lifestyle habits and wellbeing of physicians in Bahrain: a cross-sectional study

Abstract: BackgroundLifestyle habits of physicians are of paramount importance both because they influence the physician’s own health and because these habits have been shown to affect patients’ care. There is limited information on physician health and lifestyle habits in Bahrain.MethodsIn a cross-sectional study design, an anonymous self-administered questionnaire that assesses wellbeing and lifestyle habits was distributed to a random sample of 175 out of 320 primary health care physicians in Bahrain. Descriptive ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 13 publications
6
41
2
1
Order By: Relevance
“…Therefore, physically active MDs appear to have more knowledge about exercise prescription. We and others have identified the strong link between personal PA behaviors and PA counseling practices [39–42]. The findings in the present study also seem to provide support to this theory driven by the fact that one of the main barriers MDs face is not feeling confident enough to give PA recommendations in an intellectual as well as a practical level.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, physically active MDs appear to have more knowledge about exercise prescription. We and others have identified the strong link between personal PA behaviors and PA counseling practices [39–42]. The findings in the present study also seem to provide support to this theory driven by the fact that one of the main barriers MDs face is not feeling confident enough to give PA recommendations in an intellectual as well as a practical level.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, 51% of participating MDs were overweight or obese and the average sitting time was 5.6 ± 3.5 h/day, both of which are important independent risk factors for increased cardio metabolic risk and all-cause mortality [38]. In some previous studies, MDs have reported moderate to high physical inactivity rates, with similar prevalence of chronic disease and obesity as the overall population [39]. The most recent data in Colombia shows prevalence of abdominal obesity of 62% in women and 39,8% in men [35].…”
Section: Discussionmentioning
confidence: 99%
“…First, the results of the 84 eligible correlate studies are described, followed by the data on the seven intervention studies …”
Section: Resultsmentioning
confidence: 99%
“…All correlate studies were cross‐sectional, except for one longitudinal study . Half of the studies were performed in Saudi Arabia, and a large number were performed in Kuwait .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation